Creatine Phosphate in Rat Blood Platelets - Shibata, Sachiko (Thrombosis and Haemostasis, 1978)
Creatine phosphate (CP) was found in rat platelets by an assay method devised to increase the specificity and sensitivity. In this method, radioactivity of [14 C] ATP was measured after the reaction of CP with [14 C]ADP in the presence of creatine kinase. The mean value of the CP content in rat platelets was 24.8 nmoles per 109 platelets. Since the molar ratio of CP and ATP was 1:2.6, it is probable that CP plays a role in the energy metabolism of rat platelets.